Implementasi Media Pembelajaran Interaktif Taktis Meningkatkan Efektivitas Pembelajaran - Hadi, Saptono; Hermawan, Agus (Universitas Nusantara PGRI Kediri, 2024)
Research Objective The research aims to synthesize the implementation of interactive learning media in enhancing the effectiveness of education. Research Method The method employed is a Systematic Literature Review (SLR), examining primary data, texts, and content from 10 relevant sources related to the research question. The approach used in this study is qualitative descriptive, identifying accurate facts about the implementation of interactive learning media in improving learning effectiveness. Research Results The results of this study indicate that the use of interactive learning media can increase students' interest in learning. However, adequate infrastructure support and training for educators are necessary. Collaboration among various related institutions is essential to achieve effective and meaningful learning in the digital era.